2008
DOI: 10.1111/j.1365-2966.2007.12709.x
|View full text |Cite
|
Sign up to set email alerts
|

The stable magnetic field of the fully convective star V374 Peg

Abstract: International audienceWe report in this paper phase-resolved spectropolarimetric observations of the rapidly rotating fully convective M4 dwarf V374 Peg, on which a strong, mainly axisymmetric, large-scale poloidal magnetic field was recently detected. In addition to the original data set secured in 2005 August, we present here new data collected in 2005 September and 2006 August. From the rotational modulation of unpolarized line profiles, we conclude that star-spots are present at the surface of the star, bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
127
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 30 publications
15
127
2
Order By: Relevance
“…In fact, Zeeman Doppler Imaging by Morin et al (2008) has shown that the magnetic topology for an M 4 dwarf is stable on a time-scale of 1 yr. Such information on the magnetic field is crucial to understanding the means by which persistent levels of ECM emission are sustained in the magnetospheres of UCDs.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Zeeman Doppler Imaging by Morin et al (2008) has shown that the magnetic topology for an M 4 dwarf is stable on a time-scale of 1 yr. Such information on the magnetic field is crucial to understanding the means by which persistent levels of ECM emission are sustained in the magnetospheres of UCDs.…”
Section: Resultsmentioning
confidence: 99%
“…The M4 dwarf V374 Peg was selected as the first target for this campaign as it has been confirmed to possess a large-scale magnetic field with a dominant dipolar component stable over timescales > 1 year [8,9]. Most importantly, the multi-epoch ZDI observations have allowed the period of rotation of the star to be determined with sufficient accuracy to allow direct correlation of any radio light curves to the putative orientation of the large-scale magnetic field at the time of the radio observations.…”
Section: Mapping the Radio Coronae Of Active M Dwarfsmentioning
confidence: 99%
“…Turbulent dynamos operating in other stars produce strong magnetic fields and are able to transform poloidal into toroidal fields, and vice versa. Morin et al (2008) showed that the M4 dwarf V374 Peg exhibits a strong magnetic field showing only weak signatures of DR. This effect becomes even more important when stars become fully convective (Morin et al 2010).…”
Section: Introductionmentioning
confidence: 99%